1988
DOI: 10.1016/s0022-5347(17)42073-8
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Cyproterone Acetate and Low Dose Diethylstilbestrol in the Treatment of Advanced Prostatic Carcinoma

Abstract: Cyproterone acetate is a steroidal antiandrogen with weak progestational activity that results in the partial suppression of pituitary gonadotropin. We demonstrate that the associated decrease in serum testosterone is more complete and prolonged if cyproterone acetate (200 mg. daily) is combined with a low dose of diethylstilbestrol (0.1 mg. daily). The effectiveness of the combination in the treatment of prostatic carcinoma was investigated in 51 patients with stage D2 malignancy. From an initial concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Research conducted under the auspices of the European Organization for Research and Treatment of Cancer (EORTC) and based on randomized controlled clinical trials has suggested that the cardiovascular toxicity associated with CPA is much lower than for diethylstilbestrol (DES), medroxyprogesterone acetate or estramustine phosphate [2–5]. The EORTC trial comparing CPA with flutamide revealed that the difference in VTE rates between the groups was not statistically significant (relative risk 2.32, 95% CI 0.61–8.80) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted under the auspices of the European Organization for Research and Treatment of Cancer (EORTC) and based on randomized controlled clinical trials has suggested that the cardiovascular toxicity associated with CPA is much lower than for diethylstilbestrol (DES), medroxyprogesterone acetate or estramustine phosphate [2–5]. The EORTC trial comparing CPA with flutamide revealed that the difference in VTE rates between the groups was not statistically significant (relative risk 2.32, 95% CI 0.61–8.80) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Death rates vary by extent of disease but remain continuous over time. Tumor cell sensitivities vary not only by the site of spread (with progression rare in soft tissue sites) but also once the disease has been established in bone and when the first progression occurs in bone 57. Thus, to improve overall outcomes, treatments are needed that will eliminate nonproliferating cells, prevent regrowth, or promote cell death.…”
Section: How Effective Are the Standard Approaches?mentioning
confidence: 99%
“…A frequent concern regarding the clinical application of biologic, immunologic, and genetic approaches 157 Also, the radionuclide bone scan is an imprecise tool for assessing osseous disease. It is an indirect measure of activity because there is no direct visualization of the tumor, there is a lag time between an antitumor effect and a change in the scan, interpretation can be confounded by the flare phenomenon, 158 and the criteria by which bone scans are deemed to have improved or worsened vary.…”
Section: Trial Design Considerationsmentioning
confidence: 99%